2006
DOI: 10.1111/j.1939-1676.2006.tb00754.x
|View full text |Cite
|
Sign up to set email alerts
|

Myeloma‐Related Disorders in Cats Commonly Present as Extramedullary Neoplasms in Contrast to Myeloma in Human Patients: 24 Cases with Clinical Follow‐up

Abstract: Radiographic bone lesions are uncommon in cats with MRD and extramedullary presentation is common, relative to human myeloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 26 publications
8
60
2
Order By: Relevance
“…We previously reported that marked extramedullary involvement at initial clinical presentation is significantly more common in cats than in human MRD patients (67% versus ,5%, P , 0.001). 49 In the current report, we demonstrate that cats with well-differentiated tumors more commonly have extramedullary involvement than human patients with well-differentiated tumors (90% versus 20%, P , 0.0002). The multistep transformation model of human myeloma hypothesizes that the neoplastic transformation of a well-differentiated myeloma cell occurs primarily in the intramedullary compartment, and, over time, the neoplasm evolves a poorly differentiated (plasmablastic) morphology and extramedullary metastases.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…We previously reported that marked extramedullary involvement at initial clinical presentation is significantly more common in cats than in human MRD patients (67% versus ,5%, P , 0.001). 49 In the current report, we demonstrate that cats with well-differentiated tumors more commonly have extramedullary involvement than human patients with well-differentiated tumors (90% versus 20%, P , 0.0002). The multistep transformation model of human myeloma hypothesizes that the neoplastic transformation of a well-differentiated myeloma cell occurs primarily in the intramedullary compartment, and, over time, the neoplasm evolves a poorly differentiated (plasmablastic) morphology and extramedullary metastases.…”
Section: Discussionmentioning
confidence: 65%
“…Signalment, historical, clinical, clinicopathologic, and imaging features, as well as response to treatment for 24 of these confirmed cases, have been reported elsewhere. 49 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations